Konstruk Kesenjangan Budaya: Penelitian Empirik Para Manajer Perusahaan Industri Barang Konsumsi di Pasar Modal Indonesia - Tjahjadi, Bambang (Jurnal Widya Manajemen & Akuntansi, 2007)
In the era of competition, a good strategy is the most important factor for survival and growth. In order to successfully implement strategy, human capital, information capital, and organization capital within organization must be ready to support strategy. As part of organization capital, organization culture plays an important role in the success of strategy implementation. There are three ideologies within organization : (1) subjective ideologies: what other people think; (2) perceived ideologies: what people think other people think; (3) objective ideologies: part of what people think that is known , shared, and discussed with others. Culture gap exists when there is no congruence between the organization's culture and the sub-cultures of individual group members.